2004
DOI: 10.1007/s00125-004-1601-6
|View full text |Cite
|
Sign up to set email alerts
|

Disparity of autonomic control in type 2 diabetes mellitus

Abstract: Aims/hypothesis: Acute insulinaemia activates the sympathetic drive in a nonuniform manner. The extent and nature of such activation in type 2 diabetic patients who do not have neuropathy have not yet been addressed despite evidence relating sympathetic activation to cardiovascular risk. We planned to determine the magnitude and extent of the sympathetic drive and its reflex responses in patients with type 2 diabetes and fasting hyperinsulinaemia. Methods: We measured resting muscle sympathetic nerve activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 57 publications
5
47
3
3
Order By: Relevance
“…Some studies suggest that obesity is associated with increases [20], whereas weight loss is related to decreases in sympathetic nervous system activity [42]. Thus, the high levels of this protein in group O and the low levels of the protein in group O-BS may partly reflect the activity of this branch of the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that obesity is associated with increases [20], whereas weight loss is related to decreases in sympathetic nervous system activity [42]. Thus, the high levels of this protein in group O and the low levels of the protein in group O-BS may partly reflect the activity of this branch of the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that the presence of hyperinsulinemia and insulin resistance increases sympathetic nerve activity. 22 Also, C-peptide, a cleavage product of proinsulin, Blood pressure dipping and insulin metabolism M Westerståhl and C Marcus might induce the proliferation of vascular smooth muscles, 23 leading to alterations in arteriolar structure and function. In this study, we observed a very high prevalence, approximately 50%, of non-dipping among severely obese adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of one study suggest that MSNA may not be elevated in overweight humans (Huggett et al, 2005). In addition, whether the higher MSNA observed in obese individuals is genetically determined and, perhaps, part of a phenotype that is evident prior to significant weight gain and obesity is not clear.…”
Section: Weight Change and Sympathetic Neural Behaviormentioning
confidence: 97%
“…The results of numerous studies indicate that obese humans demonstrate ∼50-100% higher levels of MSNA compared with their non-obese peers (Spraul et al, 1993, Scherrer et al, 1994, Spraul et al, 1994, Gudbjornsdottir et al, 1996, Grassi et al, 2000, Weyer et al, 2000, Alvarez et al, 2002. In contrast, Hugget et al (Huggett et al, 2005) reported that MSNA was not elevated in overweight individuals. The reason(s) for this apparent discrepancy is not entirely clear but could be due, in part, to the selection of a group of overweight subjects with a primarily subcutaneous obese phenotype (see below under "6.…”
Section: Region Specific and Whole Body Sympathetic Nervous System Bementioning
confidence: 99%